Scandals and scoundrels : seven cases that shook the academy - Robin, Ron Theodore (University of California Press, 2004)
Ron Robin takes an intriguing look at the shifting nature of academic and public discourse in this incisive consideration of recent academic scandals--including charges of plagiarism against Stephen Ambrose, Derek Freeman's attempt to debunk Margaret Mead's research, Michael Bellesiles's alleged fabrication of an early America without weapons, Joseph Ellis's imaginary participation in major historical events of the 1960s, Napoleon Chagnon's creation and manipulation of a "Stone Age people," and.